Lectora Inspire-Assisted Android Application as an Integrated Ethnoscience Jamu Learning Media for Additives - Dwi Ayu Nurfaizah; Ana Yuniasti Retno Wulandari (Universitas PGRI Pontianak, 2025)
This study aims to develop and test the feasibility of Android-based science learning media developed using Lectora Inspire software and integrated with herbal ethnoscience on additive materials. Lectora Inspire media was chosen because of its ability to present material interactively and interestingly, while the integration of herbal ethnoscience elements aims to introduce local wisdom to students. This type of research is R&D (Research and Development) using the ADDIE model, which includes five stages: Analyse, Design, Development, Implementation, and Evaluate. The main instrument in data collection is a validation questionnaire using a Likert scale, which involves media experts, material experts, and science teachers as validators. The validation results showed that this media obtained an average feasibility percentage of 90.73%, which is a very feasible category. In comparison, the reliability of the data reached 92.68%, which was categorised as very reliable. This shows that the interactive learning media lectora inspire based on herbal ethnoscience on additive substances material is very feasible to use in learning. In addition, student responses also show that this media provides a more interesting and interactive learning experience, thus affecting students' interest in learning.